Peningkatan Kapasitas Kader Posyandu melalui Program KP-SEMAI Berbasis Edukasi Gizi 1000 HPK di Desa Sinar Harapan, Pesawaran - Kadek Yuke Widyantari; Novi Eniastina Jasa; Radella Ravidea (Jurnal Abdimas Kesehatan (JAK), 2026)
Stunting remains a major nutritional problem in Indonesia that has long-term impacts on human resource quality. The limited capacity of community health volunteers (posyandu cadres) in providing nutrition education and family assistance contributes to the low effectiveness of stunting prevention programs at the community level. The KP-SEMAI Program (Kader Peduli – Sinergi Edukasi Masyarakat dan Aksi Intervensi) was implemented to enhance cadres’ knowledge and skills in nutrition education using innovative educational media. The program was conducted over three months (July–September 2025) in Sinar Harapan Village, Kedondong Subdistrict, Pesawaran Regency, involving 25 posyandu cadres and 100 families with children under two years old. The activities consisted of training using the SAYANGI module (Sadar ASI, Yakin, Andalkan, Giat Menyusui), field mentoring, and evaluation through pre- and post-tests. The results showed an increase in cadres’ average knowledge scores from 55 to 75 (a 37% improvement), along with a 23% increase in family participation in posyandu activities. In addition, the program produced several innovative outputs, including the SAYANGI module, family nutrition flipcharts, and an MP-ASI educational animation video utilized by Kedondong Primary Health Center as a continuous learning medium. The KP-SEMAI program effectively strengthened community nutrition literacy, enhanced cadres’ competencies, and supported the national stunting reduction initiative at the village level